2016
DOI: 10.1177/1046878116674399
|View full text |Cite
|
Sign up to set email alerts
|

Learning Mechanics and Game Mechanics Under the Perspective of Self-Determination Theory to Foster Motivation in Digital Game Based Learning

Abstract: Background: Using digital games for educational purposes has been associated with higher levels of motivation among learners of different educational levels. However, the underlying psychological factors involved in digital game based learning (DGBL) have been rarely analyzed considering self-determination theory (SDT, Ryan & Deci, 2000b); the relation of SDT with the flow experience (Csikszentmihalyi, 1990) has neither been evaluated in the context of DGBL.Aim: This article evaluates DGBL under the perspecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 42 publications
1
56
0
5
Order By: Relevance
“…small sample size) (Gauthier & Jenkinson, 2017), this paper is limited by being one of the first to apply the Activity Theory Model of Serious Games to empirically evaluate the value-added effect of serious game design in a randomized controlled trial and, as such, we were unable to find current literature to support our findings. Recent studies have applied similar frameworks, such as the Learning Mechanics and Game Mechanics model, to support the integration of pedagogy within the game (Arnab et al, 2013;Callaghan et al, 2016;Koivisto et al, 2016;Proulx et al, 2017)-an important step for the game-based learning literature-but should extend their research by connecting measured interaction data to the serious game design to able to make concrete conclusions about the value-added effect of game design. Our ongoing research will continue to employ similar analytical approaches as described in this paper and we encourage other researchers to try similar strategies to determine the validity of the design considerations described above (Section 5.1.3).…”
Section: Limitations and Future Directions Of The Researchmentioning
confidence: 99%
“…small sample size) (Gauthier & Jenkinson, 2017), this paper is limited by being one of the first to apply the Activity Theory Model of Serious Games to empirically evaluate the value-added effect of serious game design in a randomized controlled trial and, as such, we were unable to find current literature to support our findings. Recent studies have applied similar frameworks, such as the Learning Mechanics and Game Mechanics model, to support the integration of pedagogy within the game (Arnab et al, 2013;Callaghan et al, 2016;Koivisto et al, 2016;Proulx et al, 2017)-an important step for the game-based learning literature-but should extend their research by connecting measured interaction data to the serious game design to able to make concrete conclusions about the value-added effect of game design. Our ongoing research will continue to employ similar analytical approaches as described in this paper and we encourage other researchers to try similar strategies to determine the validity of the design considerations described above (Section 5.1.3).…”
Section: Limitations and Future Directions Of The Researchmentioning
confidence: 99%
“…However, if games go beyond pure entertainment and become serious, they are purposefully developed and applied as instructional tools to transfer learning content with the aim of educating and training the player (Blumberg et al 2013). As being part of an educational programme or course, games cannot be expected to motivate students simply because they are used (Proulx, Romero, and Arnab 2017). For example, Leemkuil et al (2003) report on the pilot application of a knowledge management simulation game and showed that functionality problems and complexity can lead to dissatisfaction and that challenging, competitive and collaborative games are valued by players.…”
Section: Games and Motivationmentioning
confidence: 99%
“…From a SDT perspective it is argued that motivational and learning effects are gained if games are designed to allow for player autonomy through sufficient choices and control, competence development through task challenge and completion, and relatedness through engagement with other players (Ryan, Rigby, and Przybylski 2006;. Proulx, Romero, and Arnab (2017) propose a framework that combines game and learning mechanics with different motivational forms ( Table 1) and assert that 'the learning outcomes and motivational potential will depend on the implementation of the mechanics within the learning situation where the game is integrated' (91). Game operativeness relates to the teaching and classroom context in which the game is played and can include aspects such as time available, costs, area of application, user group, game functionality and clarity of game instruction (Frank 2007;McConville et al 2017).…”
Section: Games and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was not implemented nor tested in a real system, Prouxl et al [19] proposed to map SDT to a theoretical framework for designing serious games aimed at learning. The selected theoretical framework was the Learning Mechanics and Game Mechanics (LM-GM) [20,21].…”
Section: Sdt and Set-based Game Mechanics In Serious Gamesmentioning
confidence: 99%